Probabilistic Multi-Item Inventory Model for Chemicals in Regional Drinking Water Company - Dwipurwani, Oki; Puspita, Fitri Maya; Supadi, Siti Suzlin; Yuliza, Evi (Science and Technology Indonesia, 2024)
Inventory management of chemicals in The Regional Drinking Water Company (Perusahaan Daerah Air Minum, PDAM) is known to play an essential role in ensuring the smooth production of clean water and preventing shortages of chemicals that can affect production. At present, 2 primary models for multi-item inventory replenishment are under consideration by PDAM, namely individual and joint replenishment of items. Therefore, this study aims to evaluate the efficiency and effectiveness of individual and joint replenishment models based on uncertain demand with specific probability distribution. The results showed that a probabilistic inventory model (Q, r) with individual replenishment for chemicals in PDAM was recommended.